PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA GURU MIPA SMP KABUPATEN MAMBERAMO TENGAH - Paembang, Perty Mince; Siregar, Tiurlina (Magister Pendidikan IPA, UNCEN, 2013)
Research has been carried out with the title Headmasters leadership,The work motivation, and The work discipline for the y.rork result by MIPA teacher of Junior High School in Mamberamo Tengah regency. This reseaiyh aims for test and analyze the influence of the principal leadership, work motivation and work d.iscipline for the work result by MIPA teacher of Junior High School in Mamberamo Tengah regency. Method used in this study is descrlptive analysis methods, the data collection was conducted through quessionaires and implemented for 15 people (5 Headmasters of Junior High School and 10 Teachers of MlPA of Junior High School) in Mamberamo Tengah regency. Data analysis in this study using the help of SPSS version 16. Sampling technique was used and the method of testing techniques census data that in used in this study include test validity and rehabilitation, the classic assumption test and multiple linearregression analysis. The analyze result of headmasters leadershipwith data preparation result included very good category. The statistic calculation result indicate that value of t arithmetic = 3,045 with using significant limit 0,011 more trivial than 0,05, it means that the headmasters leadership has influence for the MIPA teacher in Junior High School in Mamberamo TenÂ¥.ah regency. The work motivation that included intrinsic and extrinsic motivation appropriate with data preparation result included good category. The statistic calculation result indicate that value of t arithmetic = 1,358 with using significant limit 0,202 more big than 0,05, it means that the work motivation doesnt has influence for the MIPA teacher of Junior High School in Mamberamc Tengah regency. The work discipline that include accuracy of time, the realization in work and discipline for the rules appropriate with the result of data preparation included *good category*. The statistic calculation result indicate that value of *t *arithmetic = 2,578 with using significant limit 0,026 more trivial than 0,05, it means that work discipline has influence for the work result of MIPA teacher of Junior High School in Mamberamo Tengah regency. The work result of MIPA teacher of Junior High School in Mamberamo Tengah regency that include educate, teach, lead, t.o aim, train, appraise and evaluate appropriate with the data preparation included good category. The statistic calculation result indicate that value of f arithme-tic n; 10.,187, with using significant limit 0,002 more trivial than 0,05. According to variable simultaneous the leadership of headmaster, work motivation and work discipline have influence for the teach ers work result. Key words : Leadership, Motivation, Work discipline,Teachers Work Result.